Kajian Jumlah Biji per Lubang Tanam dan Paket Pupuk terhadap Pertumbuhan dan Hasil Kacang Hijau (Vigna radiata L.) Varietas Vima-1 - PUTRA, I PUTU PANCA DIANTARA; WIJANA, GEDE; DINATA, KETUT KARTHA (Agrotrop : Journal on Agriculture Science; Vol 6 No 1 (2016), 2016)
Study of the Number of the Amount of Beed a Hole Planting and Packages Fertilizer onGrowth and Yield of Mung Bean (Vigna radiata L.) Varieties Vima-1. Mung bean (Vignaradiata L.) is one of bean plant – nuts for many consumption in Indonesia. The low productwas’nt cultivation techniques that supposed to, including the amount of seed each holeplanting and fertilizer giving them. The study aims to determine the amount seed hole theplanting and fertilizer best to the growth and yield of mung bean varieties vima-1. Researchcarried out in Subak Basangbe, Perean Kangin village, Baturiti – Tabanan, in October –December, 2014. The study was designed using a factorial randomized block design. The firstfactor the amount of seed a hole planting (1, 2, 3 seed), factor two of fertilizer (organicfertilizer compost, fertilizer chemical urea + TSP + KCl, organic fertilizer liquid biourin,organic fertilizer compost and fertilizer chemical urea + TSP + KCl, organic fertilizercompost and organic fertilizer liquid biourin, fertilizer chemical urea + TSP + KCl andorganic fertilizer liquid biourin). The growth of mung bean varieties Vima-1 is mainly ofplant height and number of leaves affected very real by the number of seeds planting hole andfertilizer package. Treatment of the amount of seed planting hole and fertilizer packages tovery significant effect on yield components, especially the number of pods and number ofseeds of plants on mung bean varieties Vima-1. Treatment of the amount of seed planting holeaffects most of the components of plant growth and yield components of mung bean. Thehighest yield on three planting seeds per hole that is 3,67 t / ha dry weight oven.
Keywords: mung bean, amount of seed hole planting and fertilizer